In vivo corneal confocal microscopy in multiple sclerosis: can it differentiate disease relapse in multiple sclerosis - DERİCİOĞLU, VOLKAN; AKKAYA TURHAN, SEMRA; SEVİK, MEHMET ORKUN; ERDİL, ESRA; SÜNTER, GÜLİN; AĞAN YILDIRIM, KADRİYE; TOKER, AYŞE EBRU (My University, 2023)
PURPOSE: This study aims to investigate the role of in vivo corneal confocal microscopy (IVCCM) in the detection of corneal inflammatory activity and subbasal nerve alterations in patients with multiple sclerosis (MS) and to further determine whether IVCCM can be used to detect (acute) disease relapse.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Optometri; Oftalmoloji; Optometry; Ophthalmology